PELAKSANAAN KEWAJIBAN PPH 21 DENGAN MENGGUNAKAN E-BUPOT PADA PT BANGUN ERA KONSTRUKSI - Ermanuri, Ermanuri; Dari, Erni Wulan; Miftahurrohman, Miftahurrohman; Evalina, Evalina (JURNAL LENTERA AKUNTANSI, 2023)
The implementation of the obligation of Income Tax Article 21 (PPh 21) using e-Bupot at PT Bangun Era Konstruksi has been applied and enforced starting in 2023. This is in accordance with the regulation of the Director General of Tax Number PER-2/PJ/2024, which states that the e-SPT application is no longer in use and has been replaced by e-Bupot. The research method used is descriptive qualitative research. The background is to understand the calculation, payment, reporting, and recording of the Income Tax Article 21 (PPh 21) for permanent employees at PT Bangun Era Konstruksi using the e-Bupot system that has been implemented in accordance with the applicable tax regulations in Indonesia. Based on the research results, the implementation of the PPh 21 obligation using e-Bupot at PT Bangun Era Konstruksi, from calculation, payment, reporting, and accounting recording of income tax Article 21 (PPh 21), has been carried out in accordance with the latest tax regulations in Indonesia, such as the calculation procedures that have been established.